Implementation of Self-Regulated Learning and Student Character Education during the Covid-19 Pandemic - Nini Sri Wahyuni; Istiana Istiana (Budapest International Research and Critics University, 2022)
This study aims to describe the implementation of Self-Regulated Learning and the character education of students during the Covid-19 pandemic. This research method uses literature study. The object of this research is students in Indonesia. The data collection tool in this study was to search for journals contained in several electronic media such as digital libraries and Google Scholar. The data analysis technique used in this research is annotated bibliography analysis. The results showed that the implementation of Self-Regulated Learning during online learning tended to be low and the implementation of character education experienced various challenges. Meanwhile, the learning provided by teachers during the pandemic in character education is making learning modules containing character, teachers can be able to create interesting online learning content for students, giving independent assignments containing character, implementing character education in online learning, good communication between teachers with parents, and provide rewards for positive activities carried out by students to motivate.